2018
DOI: 10.1016/j.omtn.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Association between NER Pathway Gene Polymorphisms and Wilms Tumor Risk

Abstract: Nucleotide excision repair (NER) is an essential mechanism of the body to defend against exogenous carcinogen-induced DNA damage. Defects in NER may impair DNA repair capacity and, therefore, increase genome instability and cancer susceptibility. To explore genetic predispositions to Wilms tumor, we conducted a case-control study totaling 145 neuroblastoma cases and 531 healthy controls. We systematically selected 19 potentially functional SNPs in six key genes within the NER pathway (ERCC1, XPA, XPC, XPD, XPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 41 publications
0
43
1
Order By: Relevance
“…Similarly, we have also observed that once oral cancer is established the C allele enhanced the risk of having high stage malignant disease with nodal involvement. Several other cases have reported the link of XPD A/C polymorphism with the development of different cancer in different population indicates its universal role in carcinogenesis (Du et al, 2016;Smolarz et al, 2019;Avci et al, 2018;Zhu et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, we have also observed that once oral cancer is established the C allele enhanced the risk of having high stage malignant disease with nodal involvement. Several other cases have reported the link of XPD A/C polymorphism with the development of different cancer in different population indicates its universal role in carcinogenesis (Du et al, 2016;Smolarz et al, 2019;Avci et al, 2018;Zhu et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…GTEx Portal database (https://www.gtexportal. org/home/) was used to evaluate the correlation between genotypes of the selected polymorphisms and LIN28B mRNA expression levels [24].…”
Section: Genotype and Gene Expression Correlation Analysismentioning
confidence: 99%
“…A total of 145 histopathologically confirmed cases of WT from Guangdong province (Southern China) were included in our study, [15][16][17][18][19][20][21] along with 531 unrelated, age-, gender-, and race-matched cancer-free controls. [22][23][24] Both imaging and pathological examination were used to diagnose the disease.…”
Section: Study Subjectsmentioning
confidence: 99%